2004
DOI: 10.1080/02643290342000519
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Nonword Phonological Errors in Aphasic Picture Naming

Abstract: A recent theory of lexical access in picture naming maintains that all nonword errors are generated during the retrieval of phonemic segments from the lexicon (Dell, Schwartz, Martin, Saffran, & Gagnon, 1997b). This theory is challenged by "dual origin" theories that postulate a second, post-lexical mechanism, whose disruption gives rise to "phonemic paraphasias" bearing close resemblance to the target. We tested the dual origin theory in a corpus of 457 nonword errors drawn from 18 subjects with fluent aphasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 67 publications
3
43
2
Order By: Relevance
“…Indeed, positive as well as negative results have been reported with regard to lexical frequency effects on phonological errors (see Pate, Saffran and Martin, 1987, Gordon, 2002, compared to Best, 1996, Schwartz et al, 2004, for opposite results). As argued in the introduction, following the predictions of multiple origins of phonological errors, absence of an effect of lexical factors such as frequency rather favours a post-lexical locus of impairment in both patients.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Indeed, positive as well as negative results have been reported with regard to lexical frequency effects on phonological errors (see Pate, Saffran and Martin, 1987, Gordon, 2002, compared to Best, 1996, Schwartz et al, 2004, for opposite results). As argued in the introduction, following the predictions of multiple origins of phonological errors, absence of an effect of lexical factors such as frequency rather favours a post-lexical locus of impairment in both patients.…”
Section: Discussionmentioning
confidence: 96%
“…On the one hand, studies in the framework of the double or multiple origin have attempted to demonstrate that distinct factors affect different kinds of errors, for instance neologisms and milder phonological errors, or errors produced by fluent and dysfluent aphasic patients (Valdois, 1990;Smith, 1994, 1995;Kohn, Melvold and Shipper, 1998;Wilshire and McCarthy, 1996;Romani and Calabrese, 1998;Romani and Galluzzi, 2005). On the other hand, studies in the framework of interactive activation models have sought to show that all kinds of errors are affected by the same lexical and phonological variables (Wilshire, 2002;Schwartz, Wilshire, Gagnon, and Polansky, 2004;Olson, Romani and Halloran, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different proposals provide an explanation for non-contextual segmental errors. In the context of connectionist models of language production it has been suggested that phoneme mis-selection is due to noise in the connection between lexical and phonological nodes or throughout the lexical-semantic and lexical-phonological connections (Dell et al, 1997;Foygel & Dell, 2000;Schwartz, Wilshire, Gagnon and Polansky, 2004). Alternatively, segmental errors are thought to arise because of a default mechanism attributing segments when phonological information is missing or cannot be completely retrieved (Butterworth, 1992;Kohn & Smith, 1995).…”
mentioning
confidence: 99%
“…This type of analysis has been widely applied in studies of errors made by aphasic patients in spelling and in speech (e.g. Buchwald & Rapp, 2006;Schwartz, Wilshire, Gagnon, & Polansky, 2004;Caramazza, Papagno, & Ruml, 2000;Ward & Romani, 1998b;Gagnon & Schwartz, 1997;Kay & Hanley, 1991;Neils, Roeltgen, & Greer, 1995; Serial position data 4 Papagno & Girelli, 2005;Cipolotti, Bird, Glasspool, & Shallice, 2004;Buchwald & Rapp, 2004;Cotelli, Abutalebi, Zorzi, & Cappa, 2003;Croisile & Hibert, 1998). Recently, Mactynger and Shallice (2009) showed that there are some systematic distortions of the serial position curve that the Wing and Baddeley method can introduce (see also accompanying response Wing & Baddeley, 2009), and they suggested an alternative method that we have also used and in a study of spelling errors made by deaf participants, and speech errors made by aphasic patients (Olson, 1995;Olson & Caramazza, 1999).…”
mentioning
confidence: 99%